(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
The purpose of this paper is to create and test the practical application of the business process management maturity assessment based on a case study. Maturity models are used for measuring the performance and maturity of individual functional areas or processes, as well as that of the whole organization. We propose measuring the maturity of business process management on a sample of 47 employees of one organization at two different grade levels: at the Management level and at the Professionals level. The comparative analysis of business process management maturity was performed using an ANOVA test, which allowed the evaluation of differences between the groups of respondents and using correlation matrix, which assesses the strength of the correlation between the business process maturity in the organization and six process areas (Strategy, Documentation, Optimization, Implementation, Execution, Controlling), which are constituent the maturity. The analysis of differences in the perception of business process management maturity through different employees may help better prioritize BPM development projects in an organization. The findings will be the basis for formulating recommendations for the effective raising of the business process management maturity. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.